2007
DOI: 10.1103/physrevc.76.044001
|View full text |Cite
|
Sign up to set email alerts
|

Loss and spinflip probabilities for ultracold neutrons interacting with diamondlike carbon and beryllium surfaces

Abstract: The storage of ultracold neutrons (UCN) in a combined magnetic, gravitational, and material trap is described. Wall materials investigated were diamondlike carbon (DLC) coatings on solid and flexible foil substrates as well as beryllium coatings on solid substrates. The loss coefficient per wall collision, η, and the depolarization probability β were measured simultaneously as a function of temperature (from 70 to 400 K) and energy (from 30 to 80 neV). The results at 70 K are η = (0.7 ± 0.1) × 10 −4 , β = (15.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 43 publications
2
46
0
Order By: Relevance
“…Probability of the neutron depolarization was not measured directly in these experiments, but from the reported very good magnetic resonance curves it can be concluded that the UCN depolarization probability at a single collision with the walls was not higher than in [16][17][18]. According to [24] the neutron depolarization time in the EDM experiment [21][22][23] can be estimated to be not less than τ dep ∼ 800 s. From this figure we can estimate the depolarization probability per single collision with the walls: β = l/(τ dep v) = 18/(800 × 500) ∼ 4 × 10 −5 , where l is the mean free path between two consecutive collisions, which can be found from dimensions of the neutron bottle: in the experiment [21][22][23] it was a cylinder of the internal diameter about 44 cm and height 15 cm.…”
Section: Constraints From the Ultra-cold Neutron Depolarizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Probability of the neutron depolarization was not measured directly in these experiments, but from the reported very good magnetic resonance curves it can be concluded that the UCN depolarization probability at a single collision with the walls was not higher than in [16][17][18]. According to [24] the neutron depolarization time in the EDM experiment [21][22][23] can be estimated to be not less than τ dep ∼ 800 s. From this figure we can estimate the depolarization probability per single collision with the walls: β = l/(τ dep v) = 18/(800 × 500) ∼ 4 × 10 −5 , where l is the mean free path between two consecutive collisions, which can be found from dimensions of the neutron bottle: in the experiment [21][22][23] it was a cylinder of the internal diameter about 44 cm and height 15 cm.…”
Section: Constraints From the Ultra-cold Neutron Depolarizationmentioning
confidence: 99%
“…There are two published experimental data on the ultracold neutron depolarization: [16,17] and [18], in which special experiments are described to measure this value. In both publications, for a variety of materials, the measured values of the neutron depolarization probability per one neutron collision with the walls of storage cavity were around β ∼ 10 −5 .…”
Section: Constraints From the Ultra-cold Neutron Depolarizationmentioning
confidence: 99%
See 3 more Smart Citations